The Development of Student Worksheet Based on Guided Inquiry for Transport Membrane Topic to Train Integrated Science Process Skills - Kiki Eka Purwanti; Yuliani Yuliani (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2020)
This research was aimed to produce a valid, practice, and effective student worksheet based on guided inquiry for transport membrane topic to train integrated science process skill. The development was reffered to 4D (define, design, develop, and disseminate) method without disseminate. The developed student worksheet was implemented to twenty 11th grade students of Senior High School Muhammadiyah 1 Taman. The observed method were validity method, observation of student worksheet implementation, test method, and questionaire method. Data was analyzed with qualitative and quantitative descriptive. The result of this research showed that the developed student worksheet was proved completely valid with validation score 3.87. The student worksheet practicality determined from the student worksheet implementation that gained the average of practicality score 87.67% with very practice category. The developed student worksheet was stated completely effective which determined from the achievement result of science process skill and student positive response. The achievement result of science process skill gained score 80.6% with an N-gain 0.60. Besides, the student positive response had score percentage 96%. Based on the result, it can be concluded that the student worksheet were valid, practice, effective and worthy to be used in the learning proccess. Keywords: Student worksheet, guided inquiry, integrated science process skill, transport membrane